High‐Energy LiNiO2 Li Metal Batteries Enabled by Hybrid Electrolyte Consisting of Ionic Liquid and Weakly Solvating Fluorinated Ether - Qian Liu; Jiayi Xu; Wei Jiang; Jihyeon Gim; Adam P. Tornheim; Rajesh Pathak; Qijia Zhu; Peng Zuo; Zhenzhen Yang; Krzysztof Z. Pupek; Eungje Lee; Chongmin Wang; et al. (Advanced Science)
Abstract In pursuit of the highest possible energy density, researchers shift their focus to the ultimate anode material, lithium metal (Li0), and high‐capacity cathode materials with high nickel content (Ni > 80%). The combination of these aggressive electrodes presents unprecedented challenges to the electrolyte. Here, we report a hybrid electrolyte consisting of a highly fluorinated ionic liquid and a weakly solvating fluorinated ether, whose hybridization structure enables the reversible operation of a battery chemistry based on Li0 and LiNiO2 (Ni = 100%), delivering nearly theoretical capacity of the latter (up to 249 mAh g−1) for >300 cycles with retention of 78.6% and in absence of unwanted morphological changes in both electrodes. Extensive characterization assisted by molecular dynamic simulation and density functional theory calculations reveals the function of the fluorinated ether to be far more profound than simple dilution and viscosity reduction. Instead, it induces drastic changes in Li+‐solvation environment, the consequence of which engenders simultaneous stabilization of electrode/electrolyte and interfacing via formation of respective interfacial chemistries. This study further unlocks fundamental knowledge underneath the prevailing “diluent strategy” that is extensively applied by the electrolyte researchers and opens more design space for the next‐generation electrolytes and interphases for these coveted battery chemistries.